LEGAL PROTECTION OF CHILDREN IN DIVORCE CLAIMS IN SIDOARJO RELIGIOUS COURT - Yolanda, Megan Belghis; Sulistiyantoro, Hariyo (Universitas Islam Balitar, 2024)
Divorce in family that already have children often also has an impact on their children. Divorce lawsuits can not only be filed by husbands but can also be filed by wives (contested divorce) as in case decision Number 2709/Pdt.G/2022/PA.Sda. In the petitum of this decision, the wife asked the court to terminate her marriage with her husband and stipulate that custody of her three children be given to the wife as the mother. However, based on the decision uploaded on the official website of the Supreme Court's Directory of Decisions, there does not appear to be any consideration or decision regarding the custody rights. The absence of legal considerations and decisions regarding custody of the three children may occur due to 2 (two) factors, namely technical factors and administrative factors. Divorce does not eliminate parental obligations as a form of protection of children's rights, such as a father's obligation to support his child. So that when the father does not comply with the court's decision in providing for the child, the mother can use family or litigation methods. The research method used is normative legal research (normative juridical) or also called library law research.